Mountain biking : techniques and tricks - Rosenberg, Aaron (New York : Rosen Pub. Group, 2003)
Discusses the history of the sport of mountain biking, the necessary equipment, cross country and downhill racing, and the specific techniques involved.
Background -- Equipment -- Sport -- Techniques.
Includes bibliographical references (p. 45-46) and index.
Keywords: Mountain biking -- Juvenile literature; All terrain cycling